EFEK SENYAWA AKTIF DAUN BELUNTAS TERHADAP KADAR TESTOTERON TIKUS PUTIH (Ratus norwegicus) JANTAN - Rr. Eko Susetyarini (Jurnal Gamma, 2009)
In carrying out autonomy this area needed to emphasize at the democratize principles, the roleof society, generalization and justice also pay attention the potency and area variety. Thereforeparticipation and society initiative in development needed to improve the role of society in executingdevelopment and identify potency and the local variety.This research is done in Tlogowaru of Kedung Kandang subdistrict Malang town. Target ofthis research is to describe of how society participation in identifying, planning, executing, treatmentand taking place of program are suitable with basic necessary and also government participation ofsub-district, LPMK and other organization. This research method is combining between RRA method and PRA expected can dig the information that required suitable with the target of research.Result of research indicates that the society participation in identifying the problems in societycommunity needs to be improved as form of empowering of society potency. Development is realsociety necessary and non package program forced from power center. Involvement of figuregovernmental give and give high motivation in development that have continuation is done bysociety.